Functional role of store-operated and stretch-activated channels in murine adult skeletal muscle fibres - Ducret, Thomas (Blackwell Science Inc, 2006)
In skeletal muscle, Ca(2+) is implicated in contraction, and in regulation of gene expression. An alteration of [Ca(2+)](i) homeostasis is responsible, at least partially, for the muscle degeneration that occurs after eccentric contractions in Duchenne muscular dystrophy, a disease characterized by the loss of the cytoskeletal protein dystrophin. Using patch clamp in the cell-attached configuration, we characterized the store-operated channels (SOCs) and the stretch-activated channels (SACs) present in isolated mouse skeletal muscle. SOCs were voltage independent, had a unitary conductance between 7 and 8 pS (110 mm Ca(2+) in the pipette), and their open probability increased when the sarcoplasmic reticulum was depleted by thapsigargin. These SOCs were identical to those previously described in the pathophysiology of Duchenne muscular dystrophy. Under the same experimental conditions, we detected a channel activity that was increased by applying a negative pressure to the patch electrode. The SACs responsible for this current had the same unitary conductance and current–voltage relationship as those observed for SOCs. SOCs and SACs had a similar sensitivity to pharmacological agents such as Gd(3+), SKF-96365, 2-aminoethoxydiphenyl borate and GsMTx4 toxin. Moreover, stimulation with IGF-1 increased the occurrence of the activity of both channel types. Together, these observations suggest that SOCs and SACs might belong to the same population or share common constituents. From a functional point of view, treatment of soleus muscle with SKF-96365 or GsMTx4 toxin increased its sensitivity to a fatigue protocol, suggesting that the influx of Ca(2+) that occurs through these channels during contraction is also involved in force maintaining during repeated stimulations.